LETRAMENTO MATEMÁTICO NOS ANOS INICIAIS: UMA ESTRATÉGIA DE ENSINO PÓS-PANDEMIA - Pereira, Jéssica Machado (2023)
This research is linked to the Professional Master's Degree in Science and Mathematics Teaching in the Postgraduate Program at the Franciscan University (UFN), in Santa Maria, RS. The study was developed based on the problem: What are the contributions of a pedagogical intervention based on a playful situation, on mathematical literacy in the 3rd year of elementary school? From this perspective, the objective is to analyze the contributions of a pedagogical intervention starting from a playful situation. The methodology is a qualitative, descriptive and interpretative approach, based on a pedagogical intervention. As a research instrument, we used testing, diaries and photographic records that helped us to accurately narrate daily events. For the procedure we opted for participant observation. We obtained the following results: in the elaboration of mathematical problems by students, those who were already literate in the area of mathematics were able to use literacy in problem solving, as being literate involves communication, representation through mathematical calculations, strategies, logical reasoning , the critical argument and the path taken by the student to reach the expected result, according to the playful context that was characterized by a supermarket; In the pedagogical intervention, it was possible to notice advances in relation to the Thematic Unit of Numbers, advances with significance for mathematical literacy to occur. For students who demonstrated difficulties in writing and reading, they also presented significant difficulties in the area of mathematics. We can see that there have been improvements in the teaching and learning process in the area of mathematics and literacy. It is important to highlight that each student has their own time to learn, respecting each person's learning process is part of the teacher's pedagogical work; The research provided us with changes and reflections that can improve the pedagogical practices of educators in the municipal network of Santa Maria, RS, as the intervention was beneficial as it is a tool that will assist teachers in the teaching and learning processes.